An immunohistochemical study of mesothelial cell seeding for knitted Dacron. - Bearn, P. E. (1992)
Six greyhounds underwent bilateral femoral artery replacement with knitted Dacron, one side seeded with omental digest at graft preclotting, the other acting as an unseeded control. Grafts were removed at 24 hours and two months. Tissue was examined using a monoclonal antibody (MNF116) directed against a broad range of human cytokeratins to differentiate mesothelial cells (MC) from microvascular endothelial cells (MEC), which stained only with a polyclonal antibody directed against von Willebrand Factor (anti-vWF). Cells released from omentum by collagenase stained with MNF116 and reacted poorly with anti-vWF. Identical cells were observed to be within the interstices of seeded but not control knitted Dacron. Few remained in seeded grafts (n = 2) removed at 24 hours and none at two months (n = 4).